Colposuspension in girls with refractory stress-incontinence, a critical evaluation of a last-resort treatment - van Geen, Frank-Jan; Nieuwhof-Leppink, Anka; Klijn, Aart; de Kort, Laetitia; Chrzan, Rafal (Frontiers in Urology, 2024)
IntroductionWe previously presented promising results with a Burch-type colposuspension (BC) in a heterogeneous group of girls with therapy-resistant daytime incontinence (DUI). In view of our clinical observations, we expect that a small group of girls with refractory DUI based on stress-urinary incontinence (SUI) might also benefit from a BC in order to achieve continence.ObjectiveTo assess the (long-term) effect of BC on refractory DUI in girls with SUI, and to identify predictive factors for success.Study designA retrospective chart study including all girls with refractory DUI who underwent an open or laparoscopic BC at our tertiary referral center between 2003-2017 (n=34) was performed. Patients were considered refractory after having failed all non-invasive treatment methods. The main outcome measurement was continence, expressed as the percentage of children with decreased incontinence at post-surgical follow-up without any additional treatment (complete response 4-6 months after surgery). Additionally, a cross-sectional follow-up was carried out, assessing the long-term effect of BC on DUI and patient satisfaction by means of standardized questionnaires.ResultsComplete continence after surgery was achieved in 12% (4/34) and 12% (4/34) showed a decrease in frequency of incontinence episodes. Patients with an abnormal flow pattern more often failed complete continence or improved incontinence. After a mean duration of 8 years, 84% (16/19) still experienced DUI. 68% (13/19) of those patients would opt for the BC again.ConclusionAlthough 84% of children still experienced any degree DUI after a mean duration of 8 years after BC, most patients do not regret the decision of surgical treatment. Given the limited benefit and invasiveness of the procedure, however, we discourage to routinely perform BC in children with refractory DUI and SUI. Our results should be taken into account when discussing expectations and chances of success.